Beyond reasonable doubt - Dugoni, Robert (Thomas & Mercer, 2024)
"When Jenna Bernstein, disgraced wunderkind CEO of a controversial biotech company, is accused of murdering her former partner and lover, she turns to Seattle attorney Keera Duggan to defend her. Keera is more than a master chess player who brings her intuitive moves into court--she's Jenna's childhood friend. But considering their history, Keera knows that where Jenna goes, trouble follows. Five years earlier, Keera's father successfully defended Jenna when she was tried for the killing of her company's chief scientist who threatened to go public with allegations of corporate fraud. Keera knows Jenna too well. When she was a kid, Keera saw Jenna for what she was: a manipulative and frighteningly controlling sociopath. Now, with only circumstantial evidence against Jenna, Keera is willing to bury any trepidation she might have to defend a woman she believes, this time, to be innocent. As the investigation gets underway and disturbing questions arise, Keera puts her trust in a client who swears that this time she's telling nothing but the truth. If this is all just another devious game, Keera might be working to set a murderer free"--